Effective stakeholder management and Project delivery: A case study on Mondelez cocoa life project in Antwima Mponua District - Jemima Arhin (KNUST, 2025)
A thesis submitted to the Department of Building Technology, College of Art and Built Environment, in partial fulfillment of the requirement for degree of Master of Science